Communication tools and issues among the construction project team - Nadia Izaty, Baharuddin (2015)
Communication is crucial and it gives significant influence to the outcome of the construction project whether it may be success or a failure. In the construction project, various parties involved and one of them known as project team. The objectives of this study are to identify the communication tools commonly used among the construction project team and to analyze the issues commonly arise from each communication tool used during their involvement in the project. To gather the information for this study, the researcher used two (2) types of data collection methods which are primary data sources and secondary data sources. For primary data sources, the researcher applied quantitative method which is questionnaire. This questionnaire was designed as a close-ended question and it was circulated to the respondents via email and by hand method. Meanwhile, for secondary data sources, the researcher consume literature review from published printed sources such as journals, articles and books as well as published electronic sources. The researcher use stratified random sampling type disproportionate as a sampling technique because the researcher conducted the study in four (4) group and the number of respondents are different for each group. The population of this study is 260 respondents and the sample size is 140. Respondents for this study is contractor G7, architect, civil engineer and quantity surveyor at Kedah. Results obtained from data analysis shows that most of the respondents always used telephone (either mobile phone/direct line) as a tool to communicate between them while managing a project. Using facsimiles is the lowest ranking among all the tools. The finding also shows that issue from facsimiles tool which is impractical to send lots of documents have the highest ranking among all the issues. As a conclusion, the construction project team must know suitable tool to deliver the information because from past research shows that communication is one of the factor or causes that lead to the project success or failure. For further study, the researcher hopes a research can be done to analyze on the other various tools that commonly use since the technology has evolved so much these days.